EKSEKUSI JAMINAN HAK TANGGUNGAN SECARA DI BAWAH TANGAN (Faculty of Law, University of Dr. Soetomo, 2019)
Not all creditors can return credit as promised in the contract. In an effort to guarantee the creditor's trust in paying off credit by the debtor, a collateral object is needed. In respect of collateral objects, immovable property is bound with Mortgage Guarantee institutions. But there are often problems in executing collateral objects. Normative legal research that discusses doctrinal law, uses the statutory approach and the concept approach. The purpose of this study is to find the most effective way to carry out executions that benefit both parties. Execution of collateral can be done through public auctions or underhanded execution. Execution of Credit Collateral which is burdened with Under Right Handling Rights is one of the alternatives that is considered easier and must take precedence.Keywords: Execution, Collateral, Mortgage Rights, Under the Hand